E-Waste Awareness and Disposal Practices among Higher Education Students in Kathmandu Valley, Nepal - Khatiwada, Bishal; Jariyaboon, Rattana; Techato, Kuaanan (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Electronic waste (e-waste) is a rapidly growing global challenge, with significant management deficiencies in developing countries like Nepal. While studies have examined general consumer behavior, a critical gap exists in the quantitative assessment of the youth demographic most engaged with technology. This study addresses this by providing the first comprehensive quantitative analysis of e-waste awareness, disposal practices, and barriers among higher education students in Nepal. A cross-sectional survey of 400 students in Kathmandu Valley revealed a significant attitude-behavior gap: while 65.5% were aware of e-waste and 96.2% agreed proper disposal is important, 42.0% admitted to discarding electronics in regular garbage, and only 12.2% used recycling channels. A novel and counterintuitive finding was that Master's students had significantly lower awareness than Bachelor's students (p=0.022), suggesting a potential generational shift in education. The primary barriers were lack of access to recycling programs (34.0%) and inconvenience (29.0%). Crucially, 82.5% expressed willingness to participate if convenient options were available. These findings provide unprecedented empirical evidence of the disconnect between knowledge and action, highlighting the urgent need for improved infrastructure and targeted educational policies to leverage positive student attitudes for sustainable e-waste management in Nepal.